Better to Die Young": A Hermeneutic Analysis of Protest and Moral Critique in Remy Sylado’s Mbeling Poetry - Rapi, Muhammad; Ridwan, Ridwan; Bunga , Vionanda Toding (Tamaddun Life, 2025)
This study analyzes the socio-political critique embedded in Remy Sylado’s poem Lebih Baik Mati Muda through Friedrich Schleiermacher’s hermeneutic framework, specifically integrating grammatical and psychological interpretations. As a pioneering figure in the Indonesian Mbeling poetry movement, Sylado strategically employed colloquial language, provocative diction, and emotionally charged imagery to confront systemic corruption, authoritarianism, and moral decay during Indonesia’s New Order regime. Using qualitative descriptive methodology, the analysis first examines the poem’s grammatical elements such as diction, rhetorical structures, and repetition to reveal how linguistic deviation amplifies the poet's socio-political critique. Subsequently, psychological interpretation uncovers deeper emotional dimensions, highlighting how the narrative voice conveys generational despair and moral urgency. Findings indicate that Sylado’s recurrent phrase Lebih baik aku mati muda ("Better that I die young") symbolizes an existential and ethical ultimatum, articulating a powerful stance against oppressive societal conditions. The study contributes methodologically by applying Schleiermacher’s dual hermeneutic approach to Indonesian protest poetry, theoretically by deepening scholarly understanding of poetry's role in social resistance, and practically by underscoring poetry’s educational potential in fostering critical literacy and civic engagement. Future research is recommended to expand comparative and multimodal analyses of protest poetry, enhancing understanding of its cognitive and emotional effects across different contexts.